The Importance of the Relation between Knowledge Sources Frequency Use and the Level of Customer Knowledge Utilisation in the ICT Sector New Product Development Process - Anna SZWAJLIK (Communications of International Proceedings, 2021)
The aim of this article is to discuss the relationship between knowledge sources and the level of knowledge about customers declared by ICT industry managers organization. In the last decade, external sources of knowledge that provide valuable, up-to-date information, have gained importance. This enables enterprises to, inter alia, use existing customer's resources to develop new products. For the purposes of achieving the set objective, quantitative research was carried out using the CAWI and CATI survey method on a sample of 400 enterprises from the ICT sector. The research subject was to determine the relationship between frequency of usage and diversity of sources with the level of the declared knowledge "about, for and from the customer" and "co-created with the customer" in the surveyed organizations. The research results showed that there is a positive correlation between the frequency of using various sources and the level of knowledge of the surveyed managers. Enterprises from the ICT industry implement new IT projects tailored to the individual needs of customers. Companies should acquire and share with customers knowledge from various sources in order to obtain the optimal level of customer knowledge in the organization.
Keywords: Customer Knowledge Management; sources of customer knowledge; new product development and ICT sector.